Use of Library Course for Undergraduates’ Better Usage of Library Resources in Nigeria - Stanley Omondiale Unuabor; Godsent Christopher Oyakhilomen Oseghale; Blessing Anegbemhente Usiedo (Research Highlights in Language, Literature and Education Vol. 6, 2023)
The major focus of this study is to ascertain how undergraduates in the Faculty of Education, University of Ibadan use the library and its resources in spite of the user education gained through the use of library course. In every academic environment, the library, users as well as information resources are very important components for realization of academic set goals. Therefore, the effectiveness of academic library is a function of a healthy interaction between the users, library staff, information resources and other components that make up the library system. Structured questionnaire was used for the collection of data. The population of the study focused on was the undergraduates of the faculty of Education, University of Ibadan. The target population was from six out of seven departments in the Faculty of Education. The nature of user education programme, timing and content were the major factors that caused undergraduates dissatisfaction in using the library resources. Therefore, the findings adjudged undergraduates as non-frequent users of the library. The lecturers in charge of the library use course, reference librarians, and all other library professionals and library staff who organise library orientation should all participate in the teaching/training of undergraduates in some way, while keeping the user education program’s objectives in mind. Failure to accord Use of Library the status of a full-fledged GENERAL STUDIES (GES) course with high units was found as the most significant factor limiting effectiveness of user education programme through the Use of Library. Therefore, In order to increase seriousness among undergraduates in Faculty of Education in Universities and other higher institutions generally, it is advised that "Use of Library Course" be separated from the "Use of English Course" in the GES/GST/GNS 101 and have USE OF LIBRARY as a full-fledged course with a high unit credit load. The curriculum should also be based on more of a practical approach than a purely theoretical/essay approach.